Peruvian Fur Seals as Archivists of El Niño Southern Oscillation Effects - Edwards, Mickie R.; Cárdenas-Alayza, Susana; Adkesson, Michael J.; Daniels-Abdulahad, Mya; Hirons, Amy C. (Frontiers in Marine Science, 2021)
Peru’s coastal waters are characterized by significant environmental fluctuation due to periodic El Niño- La Niña- Southern Oscillation (ENSO) events. This variability results in ecosystem-wide food web changes which are reflected in the tissues of the Peruvian fur seal (Arctocephalus australis). Stable isotope ratios (δ13C and δ15N) in Peruvian fur seal vibrissae (whiskers) are used to infer temporal primary production and dietary variations in individuals. Sea surface temperature anomaly (SSTA) recordings from the Niño 1+2 Index region captured corresponding ENSO conditions. Fluctuations in δ15N values were correlated to SSTA records, indicating that ENSO conditions likely impact the diet of these apex predators over time. Anomalous warm phase temperatures corresponded to decreased δ15N values, whereas cold phase anomalous conditions corresponded to increased δ15N values, potentially from upwelled, nutrient-rich water. Vibrissae δ13C values revealed general stability from 2004 to 2012, a moderate decline during 2013 (La Niña conditions) followed by a period of increased values concurrent with the 2014–2016 El Niño event. Both δ13C and δ15N values were inversely correlated to each other during the strongest El Niño Southern Oscillation event on record (2014–2016), possibly indicating a decline in production leading to an increase in food web complexity. Lower δ13C and δ15N values were exhibited in female compared to male fur seal vibrissae. Findings suggest ENSO conditions influence resource availability, possibly eliciting changes in pinniped foraging behavior as well as food web of the endangered Peruvian fur seal.